THE ROLE OF EXOGENIC GROUNDWATERS IN KIMBERLITE FORMATIONS - Malov A.I. (My University, 2004)
The point of view that exogenic groundwaters participate in the formation of kimberlite rocks in Yakutia and South Africa is shared by many researchers. Data on the isotopic composition of minerals in these kimberlite rocks are usually presented in order to substantiate this assumption. For the Mezen Syncline, we have obtained data on the carbon and oxygen isotopic compositions of a carbonate sill that intrudes argillites of the Vendian Mezen Formation along the hydraulic crack. The δ13C value ranges from -3.7 to -10.1‰ (PDB), whereas the δ18O value ranges from 21.9 to 24.4‰ (SMOW). The sill is composed of porphyry kimberlite with olivine pseudomorphoses replaced by serpentine and calcite.(Russia).